"Getting placed" in time: Responsibility talk in caseworker-client interaction. Issue 3 (15th June 2015) - Matarese, Maureen
Abstract : This study describes one caseworker's construction of responsibility through her interactions with three homeless clients in an urban homeless shelter, revealing the significant impact of the shelter, shelter policy, and personal contexts on the construction of responsibility in talk. It explores how responsibility is constructed through a series of discursive choices, including deontic modality, personal pronouns, expressions of time and space, and accounts. These discursive choices expose the ways in which the caseworker's responsibility talk changes depending on the category of client. Specifically, the study compares the caseworker's responsibility talk with an undocumented homeless client to her responsibility talk with long-term staying clients. Given policy mandates to place long-term clients (in shelter nine months or longer) more quickly, responsibility talk with these clients as they near the nine-month benchmark is more aggressive. The study shows how the caseworker's talk with the new undocumented client surprisingly resembles her talk with the long-term clients nearing the nine-month benchmark. She discursively treats this new undocumented client like persisting ones. 'Imagined time' and 'imagined space' are introduced to aid in describing the projected, future non-compliance of a new undocumented client as established in the caseworker's responsibility talk.